Pengaruh Kualitas dan Hubungan Antara Keterampilan Sumber Daya Manusia Terhadap Penggunaan Smartphone Produk Ios dan Android di Wilayah Kabupaten Banyumas dan Kebumen - Pujianto Pujianto (SMARTINDO, 2025)
This research aims to analyze the influence of the quality and skills of human resources (SDA) on the use of iOS and Android-based smartphones in the Banyumas and Kebumen districts. Along with the rapid development of technology, smartphones have become important devices to support various daily activities, both in the personal and professional realms. On the other hand, utilizing the features and applications available on smartphones often depends on the quality and skills of human resources. This research uses a quantitative approach with a survey method involving 100 respondents from both regions. Respondents were selected purposively based on certain criteria, such as educational background, occupation, digital skills and preference for iOS and Android.